Inclusive Leadership Dynamics to Enhance Motivation and Retention of Older Employees in Modern Organizations - Darmawan, Didit (Metromedia, 2025)
The growing presence of older adults in the global workforce structure demands organizations to adopt leadership styles that are fair, supportive, and empowering. This study examines how inclusive leadership contributes to enhancing work motivation and employee retention among senior workers. A quantitative approach was employed, involving respondents aged over 50 from ten companies across various sectors in Surabaya. Linear regression analysis was used to assess the relationship between inclusive leadership as the independent variable and two dependent variables: work motivation and retention. The findings highlight the pivotal role of inclusive leadership in fostering motivation among older employees, which in turn strengthens their loyalty and performance. The implications emphasize the importance of inclusion-based HR strategies and the need for organizations to invest in cross-generational leadership development. This study aims to inform HR policy reforms, particularly in building organizational resilience and promoting sustainability through age diversity appreciation.